IMPLEMENTASI MASHLAHAH AL-MURSALAH DALAM KASUS PERKAWINAN - Ali Mutakin (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2018)
Al-Quran and Hadith are sources and arguments in Islamic law whose existence has been agreed upon by the ulama. In addition to these two arguments, there are several propositions whose existence is still disputed, one of which is the mashlahah al-mursalah. The application of the concept of mashlahah al-mursalah in determining the legal status of a problem rests on the basis of benefit which becomes the spirit of the Qur'an and Hadith. In marriage, cases of marital marriage and restrictions on the age of marriage, are not formally explained by the Qur'an or Hadith, but based on the benefits contained in it in accordance